A Spatial Analysis Of Tuberculosis Incidence Trends And Environmental Determinants In Depok City In 2022–2024 - Muhammad Baskoro; Artha Prabawa; Zanastia Sukmayanti (Jurnal Riset Kesehatan, 2026)
Tuberculosis (TB) remains a major public health problem in Indonesia and globally. TB is transmitted through airborne droplets inhaled from individuals with active TB. Transmission risk increases in densely populated areas, poor ventilation, and settings with high social interaction, such as Depok City. Persistently high TB prevalence reflects challenges in treatment success and community-based prevention. This study aims to analyze trends and spatial patterns of TB incidence in Depok City from 2022 to 2024 and their relationship with population density and hand washing behavior with soap (HWWS). A spatial descriptive study was conducted using secondary data on TB cases and HWWS from the Depok City Health Profile, and population density data from Depok City in Figures (2022–2024). TB cases were concentrated in districts with high population density, particularly Tapos, Sukmajaya, Pancoran Mas, and Cimanggis. HWWS showed no clear spatial association with TB incidence. Population density was identified as the main determinant of TB distribution in urban areas. Therefore, region-based TB control strategies supported by spatial analysis are needed to improve intervention prioritization and effectiveness.